Variabilidade genética, morfológica e fitoquímica de genótipos de Opuntia e Nopalea - Alves, Francisco Abel Lemos (2015)
The cactus pear of the Opuntia and Nopalea genres are species of plants very cultivated in the semiarid region of Brazil, mainly for forage production for animals in the dry season. The cladodes of the plant has been considered per long time an important source of nutrients for human and animal alimentation, besides have beneficial properties for health. Because of great genetic diversity of these genres, with about 300 species, there is a need to characterize the varieties grown in Brazil in order to get nutritionals information and bioactive properties. The objective of this study was to characterize the genetic and temporal variability of chemical and nutritional profile of cladodes of varieties of cactus pear of the genres Opuntia and Nopalea cultivated in semiarid region of Brazil; evaluate the potential antioxidant and cytotoxic of ethanol crude extracts of cladodes of these varieties, against human cancer cells; besides, characterize the genetic diversity through characteristics phenotypic, chemical and nutritional, and determine the correlation and importance of these characteristics in the variability between genotypes, using multivariate techniques. The researches were conducted with seven cactus pear varieties (IPA-100003, IPA-100004, IPA-200021, IPA-200205, IPA-200008, IPA-200149 and IPA-200016) in two seasons, dry and rainy. The plants were cultivated under rainfed conditions in the experimental station of Instituto Agronomico de Pernambuco (IPA), located in Arcoverde-PE. Plants were analyzed by 19 morphologic characteristics and 20 chemical and nutritional attributes. The results of the study of the chemical and nutritional profile of the cladodes of cactus pear varieties confirm the nutritive value so much in animal nutrition how much in human nutrition. The components chemical and nutritional of the cactus pear have a wide variation so much in its composition how much in its content, and vary between plant species studied, within the same species, among cladodes within the genotype and season collect material. The studies confirmed that the secondary metabolites (bioactive compounds) present in the cactus pear have antioxidant and cytotoxic activity against cells of human cancer studied (HCT-116-colon rectal, SF-295-glioblastoma and OVCAR-8-ovarian carcinoma). These substances are of the class of phenolic compounds (phenolic acids and flavonoids) and/or sterols identified in the cladodes. Just as in the chemical composition, antioxidant and cytotoxic activity of the extract ethanol crude of cladodes varies between plant species studied, within the same species, seasons of the year and types of cancer cells. The results of the study of genetic diversity using phenotypic, chemical and nutritional characteristics indicated that the water content, fresh weight, flavonoid content and potassium of the cladodes were the characteristics that most contributed to the genetic variability between genotypes. These characteristics are significantly correlated to dry weight, width, length, area, nitrogen free extract and phenolic compounds of cladodes. This research also grouped the varieties according to their similarities, in two to five groups different, facilitating the choice of viable crosses between genotypes, aiming genetic gains between the characteristics of interest.